Research on real-world knowledge mining and knowledge graph completion (I): overview of re-al-world data and knowledge map - Xu-Hui LI; Si-Yu YAN; Mu-Kun CHEN; Hai-Feng ZHU; Jie-Jun TAN; Kuang GAO; Yong-Bo WANG; Qiao HUANG; Xiang-Ying REN; Ying-Hui JIN; Xing-Huan WANG (Yixue xinzhi zazhi)
The real-world data comes from the real medical environment, which can reflect the med-ical process and the patient's health status under real clinical conditions, and can be used as an important source of evidence and knowledge. As a semantic network, knowledge map can be used to organize, pre-sent and reason medical knowledge. The combination of real-world data and knowledge map can better supplement, display and use medical knowledge. At present, using real-world data to build a medical knowledge map or using real-world data to complete the medical knowledge map are the main ways of combining the two applications. When carrying out the application research on the combination of re-al-world data and medical knowledge map, attention should be paid to the issues about the multidiscipli-nary team collaboration, patient privacy protection and data standardization.